Analisis Bahasa Figuratif dalam Novel Lonte Pageu Karya Adam Zainal - Nurul Izzah; Trisfayani, Trisfayani; Rasyimah, Rasyimah; Wulanda, Wulanda (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to analyze the use of figurative language in the novel Lonte Pageue by Adam Zainal. The method employed is descriptive qualitative, which is commonly used to analyze literary texts. The data collection technique applied in this research is the reading and note-taking technique, where the researcher reads through the novel and notes down relevant instances of figurative language. The data used in this study consist of sentences or phrases containing figurative language found in Lonte Pageue. The source of the data for this research is the novel Lonte Pageue by Adam Zainal, which serves as the primary material for analysis. The data analysis techniques applied include data reduction, data presentation, and conclusion drawing. The findings and discussion regarding figurative language in Lonte Pageue revealed a total of 85 instances of figurative language. These instances consist of 31 rhetorical figurative language expressions and 54 tropes. The rhetorical figurative language includes alliteration, euphemism, litotes, hyperbole, and paradox, while the tropes include simile, metaphor, personification, synecdoche, metonymy, antonomasia, irony, and antiphrasis. The results of the analysis indicate that rhetorical figurative language is the most frequently found, with 31 instances, while tropes are the least frequently identified, with only 54 instances. This study provides a comprehensive understanding of how figurative language is employed in Lonte Pageue, which contributes to the development of literature analysis.